2016
DOI: 10.1007/s00535-016-1299-5
|View full text |Cite|
|
Sign up to set email alerts
|

Action and function of Wnt/β-catenin signaling in the progression from chronic hepatitis C to hepatocellular carcinoma

Abstract: Hepatitis C virus (HCV) infection is one of the leading causes of hepatocellular carcinoma (HCC) worldwide but the mechanistic basis as to how chronic HCV infection furthers the HCC process remains only poorly understood. Accumulating evidence indicates that HCV core and nonstructural proteins provoke activation of the Wnt/β-catenin signaling pathway, and the evidence supporting a role of Wnt/β-catenin signaling in the onset and progression of HCC is compelling. Convincing molecular explanations as to how expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 132 publications
(108 reference statements)
1
70
0
Order By: Relevance
“…ZEB1 has the most consistent inverse correlation with E‐cadherin across different types of carcinomas, thus showing involvement in cancer cell motility. In the further research, β‐catenin is the core molecule in activation of the Wnt signaling pathway, and its content and localization are regulated by the APC/Axin/GSK3β complex . The IF assay showed that miR143HG could assemble β‐catenin on the membranes of HCC cells and prevent its nuclear translocation and subsequent activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZEB1 has the most consistent inverse correlation with E‐cadherin across different types of carcinomas, thus showing involvement in cancer cell motility. In the further research, β‐catenin is the core molecule in activation of the Wnt signaling pathway, and its content and localization are regulated by the APC/Axin/GSK3β complex . The IF assay showed that miR143HG could assemble β‐catenin on the membranes of HCC cells and prevent its nuclear translocation and subsequent activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the further research, β-catenin is the core molecule in activation of the Wnt signaling pathway, and its content and localization are regulated by the APC/Axin/ GSK3β complex. 34 The IF assay showed that miR143HG could assemble β-catenin on the membranes of HCC cells and prevent its nuclear translocation and subsequent activation. These results from several aspects indicate that miR143HG affects HCC invasion and migration through the Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Core protein has been shown to decreases the expression of the Wnt antagonists; dickkopf and secreted frizzled-related protein by recruiting DMT1, and HDAC1 to their transcription start sites. 138,139 The NS5A protein activates PI3K/Akt signaling, leading to the inactivation of GSK3β and subsequently reducing the degradation of β-catenin. 140,141 The activation of c-Myc oncogene through Wnt/β-catenin pathways has been shown to promote HCC in HCV transgenic mice model.…”
Section: The Wnt/β-catenin/c-myc Pathwaymentioning
confidence: 99%
“…Human HCC cell lines Hep3B, HepG2, HepaRG, Huh6, Huh7, PLC/PRF/5, SNU398, SNU182, and SNU449 were cultured as reported previously (7). Identity of all cell lines was confirmed by short tandem repeat genotyping.…”
Section: Cell Linesmentioning
confidence: 99%